Incidence of Acute Kidney Injury (AKI) Secondary to Acute Gastroenteritis in Patients Presenting to Ayub Teaching Hospital, Abbottabad - Nighat Jamal, Faizan Banaras, Mahnoor Ashfaq, Tehrim Tahir, Iqra Jadoon, Ali Raza (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute kidney injury is a decrease in kidney functions that results in reduced glomerular filtration rate, retention of nitrogenous waste products, and disturbances of extracellular volume and electrolytes. The incidence of acute kidney injury is about 20-200 per million, about 7-18% of patients in a hospital.2 Acute diarrheal diseases are one of the important causes of preventable acute kidney injury. Improper fluid deficit restoration in diarrheal diseases results in acute kidney injury, manifested as decreased renal function and a rise in serum creatinine level with or without reducing urine output. The injury may range from mild to severe renal dysfunction; sometimes requiring renal replacement therapy.4The rapid and effective restoration of extracellular fluid can prevent acute kidney injury. Materials and Methods: An observational cross-sectional Study, among patients with acute diarrheal illnesses presented to all medical units (A, B, C &D) and the emergency department of Ayub Teaching Hospital, Abbottabad. A total of 140 patients presented in 3 months duration from 1st July – 30th Sep 2022. Data were analyzed by using SPSS 16 Results: In the sample size of 140 patients, the minimum age was 14 years and the maximum age was 70 with a mean of 38 years with a standard deviation of +/- 14 y. Among 140, 80 patients were male and 60 patients were female. Out of 140 patients, 47 were having hypertension, 19 were diabetic and 16 were known, cardiac patients. Urine output of 13 (9.3%) patients was less than 100ml/day, while 46 (32.9%) patients were having 100-400ml/day, 37 (26.4%) patients was having 400-1200ml/day and 44 (31.4%) patients had greater than 1200ml/day. The serum creatinine level was greater than 2.8mg/dl (more than 2 times normal) in 35 patients (25%), and 18 patients were having creatinine levels in the range of 1.5-2.8mg/dl (up to 2 times greater than normal) and 87 patients had creatinine levels in the normal range (0.7-1.4mg/dl). Out of 140 patients, 41 (29.3%) presented to the tertiary care hospital in shock (systolic blood pressure less than 90mmhg), 96 (68.6%) were normotensive and 3 (2.1%) patients were hypertensive. Conclusion: The incidence of acute kidney injury in patients presenting with acute gastroenteritis to a tertiary care hospital is 25%, due to hypovolemia caused by fluid losses in acute diarrheal illnesses. It can be prevented by prompt diagnosis and treatment by fluid administration. Keywords: Acute kidney injury (AKI), Acute renal failure(ARF), Eschericia coli (E.Coli) RIFLE (Risk, Injury, Failure, Loss, End Stage kidney disease)